COMPARAÇÃO DOS GRAUS DE DESAFIO DE EIMERIA COM ALTERAÇÃO DA PERMEABILIDADE GASTROINTESTINAL E MORFOLOGIA INTESTINAL DE FRANGOS DE CORTE - SOUZA, GIOVANA CAMARGO DE (2023)
The purpose of this study was to see how graded Eimeria challenges affected gastrointestinal permeability, intestinal morphology, and intestinal lesion scores in broiler chickens. This study included four groups of ten chickens each, each with a distinct Eimeria treatment dose, such as high-dose challenge, medium-high, and medium-low. Five days after the challenge, intestinal lesions and gastrointestinal permeability were assessed. The results showed that increasing the Eimeria challenge dose resulted in a considerable decrease in intestinal villi height, ratio villus size and crypt depth and globet cells. Furthermore, after the challenge, there was a considerable increase in gastrointestinal permeability. In conclusion, the higher the Eimeria doses given to the chickens, the more serious the gut damage seen in numerous gastrointestinal health indices. An ideal Eimeria-challenge dose of medium-low or medium-high levels of mixed Eimeria oocysts is proposed to construct a clinical challenge model for future investigations testing dietary interventions.